Complement regulatory proteins: Candidate biomarkers in differentiating tuberculosis pleural effusion - Tang, Huan; Hu, Xinyue; Li, Li; Deng, Shuanglinzi; Jiang, Yuanyuan; Luo, Lisha; Cai, Runjin; Yang, Yifei; Wu, Chendong; Gong, Xiaoxiao; Feng, Juntao (Frontiers in Immunology, 2023)
Background and aims Complement activation is essential for tuberculosis pleural effusion. However, little is known about the value of complement regulatory protein (CD46, CD55, and CD59) in the differential diagnosis of tuberculosis. Materials and methods Ninety-nine patients with exudative pleural effusion admitted to Xiangya Hospital of Central South University from June 1, 2021to November 14, 2022 were enrolled. The expression levels of soluble CD46 (sCD46), soluble CD55 (sCD55), and soluble CD59 (sCD59) in pleural effusion were quantified by enzyme-linked immunosorbent assay, and the receiver operating characteristic (ROC) curves were plotted to evaluate the diagnostic and co-diagnostic values. Results The ADA level is higher in TPE patients than non-TPE patients. It is well-found that TPE patients had lower levels of sCD46, sCD55, and sCD59 compared with non-TPE patients. Moreover, the expression of sCD46, sCD55, and sCD59 in pleural effusion was negatively correlated with ADA. In addition, the diagnostic efficacy of sCD46, sCD55 and sCD59 was comparable to that of ADA, with 0.896, 0.857, 0.858 and 0.893, respectively. Furthermore, combine detection of sCD46, sCD55, sCD59 and ADA could improve the diagnostic accuracy. Conclusions Complement regulatory factors (CD46, CD55, and CD59) were validated by this project to be promising candidate biomarkers for the diagnosis of TPE with high accuracy. The combination of the CD46, CD55, and CD59 and ADA assay exist a better diagnostic value in TPE.